A Class of Estimators for Finite Population Mean in Double Sampling under Nonresponse Using Fractional Raw Moments - Manzoor Khan; Javid Shabbir; Zawar Hussain; Bander Al-Zahrani (Journal of Applied Mathematics)
This paper presents new classes of estimators in estimating the finite population mean under double sampling in the presence of nonresponse when using information on fractional raw moments. The expressions for mean square error of the proposed classes of estimators are derived up to the first degree of approximation. It is shown that a proposed class of estimators performs better than the usual mean estimator, ratio type estimators, and Singh and Kumar (2009) estimator. An empirical study is carried out to demonstrate the performance of a proposed class of estimators.